Illumination conditions at the lunar south pole using high resolution Digital Terrain Models from LOLA - Gläser, P.; Scholten, F.; De Rosa, D.; Figuera, R.M.; Oberst, J.; Mazarico, E.; Neumann, G.; Robinson, M. S. (Icarus, 2014)
The illumination conditions of the lunar south pole are investigated using a geometrically adjusted, 20 m/pixel Digital Terrain Model (DTM) from laser tracks of the Lunar Orbiter Laser Altimeter (LOLA). Several comparisons with Narrow Angle Camera (NAC) images have been made to cross-validate the results. Illumination conditions were first evaluated over a region of 20 x 20 km over a one-year period (October 22, 2018 - October 22, 2019) at surface level and 2 m above ground. Three potential landing sites are investigated in more detail. A 19-year study covering the lunar precessional cycle was carried out at surface level, 2 and 10 m above ground for a site found at "Connecting Ridge", the ridge connecting the Shackleton and de Gerlache crater. This area was found to be an ideal site for future landing missions with respect to illumination conditions. We identified locations receiving sunlight for 92.27% of the time at 2 m above ground and 95.65% of the time at 10 m above ground. At these locations the longest continuous periods in darkness are typically only 3-5 days. (C) 2014 Elsevier Inc. All rights reserved.